Strengthening The Role and Legal Protection of Commitment Making Officials in Government Goods/Services Procurement - Yana Astuti; Samian Samian; Sarwono Hardjomuljadi (International Journal Labs, 2025)
Commitment Making Officials (PPK) play a crucial role in the entire cycle of Government Procurement of Goods/Services (PBJP) in Indonesia, starting from planning, contract binding, to handing over work results. This strategic position, which is always related to decision-making with implications for state budget spending, makes the PPK very vulnerable to legal risks, both in the form of contract disputes, maladministration, and alleged corruption. This research aims to analyze the authority and responsibilities of the PPK in the PBJP and formulate a strategy for optimizing governance and legal protection for the PPK to prevent irregularities and minimize potential state losses. The research method used is normative juridical with a legislative approach and a conceptual approach. The results of the study show that optimizing the role of PPK requires: strengthening managerial and legal competence; structuring of work mechanisms that are more accountable and transparent; and the formation of a professional support team (legal, technical, and financial) as an instrument to mitigate legal and financial risks for the PPK in the implementation of the PBJP contract.